First case report of spontaneous posterior fossa subdural hemorrhage – A rare cause of neonatal encephalopathy. (September 2019) - Sreedhara, M.S.; Ninan, Binu; Prakash, A.; Visvanathan, K.; Shekhar, Ravi; Usha Devi, R.
Highlights: First case report of posterior fossa subdural hemorrhage in term neonate without any risk factors. Insufficient evidence for optimal timing and need for surgical evacuation. Decision should be made on a case to case basis. MRI, the modality of choice for neonatal encephalopathy should include Gradient recalled echo (GRE) sequences to identify haemorrhage. Abstract: Posterior fossa subdural hemorrhage (PFSDH) in term neonates is rare and unknown in the absence of obvious trauma. Its management is challenging and decided case to case basis. Here we report two cases of posterior fossa subdural hemorrhage in term babies with normal transition at birth and presenting later with neonatal encephalopathy. First baby was born by elective caesarean section and the second baby by assisted vaginal delivery. They presented at 60 h and 48 h respectively. Both babies had similar clinical presentation in the form of poor feeding, shrill cry and posturing. But they had contrasting clinical course with features of brainstem compression in the first baby requiring ventilation. Coagulation workup was normal in the first baby but fibrinogen level was low in the second baby. Magnetic resonance imaging of the first baby showed PFSDH with tonsillar herniation while in the second baby, there was no midline shift or herniation associated with the PFSDH. Management was tailor made to suit the clinical course and imaging findings. Craniotomy and clot evacuation was done in the first case and in the second baby, management was conservative. Neurological examination was normal at discharge. Both are developmentally normal on follow up. There is no evidence of hydrocephalus in both. Management of PFSDH depends on clinical course and MRI findings. Timely intervention leads to good outcome.